Effect of hops oil on sunflower oil thermal stability - Çelebi, Kamil; Cerit, İnci; Demirkol, Omca (Progress in Nutrition, 2022)
The aim of this study was to compare the effects of hops oil and butylated hydroxytoluene (BHT) on the thermal stability of sunflower oil. Oil samples were subjected to heat treatment at 180oC for 5 min and this process was repeated ten times. Free fatty acid (FFA), peroxide (PV), p-anisidine (p-AV), conjugated dienes (CD) and trienes (CT) values,  induction time (IT) and fatty acid composition (FAC) were investigated after 0, 2, 5 and 10 heating cycles to evaluate chemical changes during heating. Antioxidant activities of oil samples were evaluated using DPPH radical scavenging and β -carotene bleaching assays. According to the results, the change in the FFA value of sunflower oils was not significant at the end of the ten heating cycles. The effect of the hops oil on PV and p-AV was found to be similar to that of BHT. Hops oil (1200 ppm) added sample (1.0) gave the closest CD value to the BHT group (0.8). Addition of BHT and hops oil prolonged the induction time of sunflower oil. Total monounsaturated fatty acids increased while polyunsaturated content decreased in all samples. Moreover, hops oil exhibited significantly higher antioxidant activity in sunflower oil compared to control.